Penguatan Kapasitas Akademisi dan Mahasiswa melalui Dialog dan Pelatihan Reflektif Pembangunan Daerah Menuju NTB Makmur Mendunia - Suriadiata, Irpan (Insan Kreasi Media, 2025)
This community engagement program aims to strengthen the capacity of academics and students through dialogue and reflective training in support of regional development aligned with the vision of NTB Prosperous and Globally Recognized. The initiative stems from the growing need for active academic participation in development, which should not only focus on technical skills but also emphasize the cultivation of critical awareness and analytical capabilities.The program employed a participatory approach by integrating Participatory Learning and Action (PLA), Critical Reflective Practice, and Collaborative Engagement. It was implemented within the higher education environment, involving lecturers and students across various study programs. The activities included reflective dialogues with resource persons from academia, development practitioners, and local government, as well as case-based reflective training. Evaluation through pre-tests and post-tests demonstrated a significant improvement in participants’ understanding of sustainable development concepts, critical awareness, and collaborative skills. Participants were not only able to identify regional development challenges but also to formulate strategic recommendations aligned with the vision of NTB Prosperous and Globally Recognized. The results reinforce the theory that community participation—particularly from academics and students—is a key element in regional development. The scientific novelty of this program lies in its reflective approach combined with academic dialogue, which has rarely been the focus of previous community engagement initiatives. Accordingly, this program contributes to the creation of a collaborative learning ecosystem that fosters synergy among academics, students, government, and society in advancing sustainable regional development.